(3GdeMdi TQM GdeLdis - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg Hbhdg (B: (3Yf CHj HcQI bGd Udi QShd Gddg Udi Gddg Ydjg hSde ai Nha GdXgQ aUa HYVge Ndag hHYVge HERGA GdYOO s
(3BNQgG (B:s
(3jfJgi CKfGA HGH GdRcGI Hbhdg (B: (3hbO PcQfGgG ai HGH PcQfG ChdGO GdeGTjI hCeG JbSje CHj MfjaI heGdc hGdTGaYi adGjMaX Yf CMO ef GdUMGHI QVi Gddg Yfge s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis